2006
DOI: 10.1177/0146167205276118
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mood on the Search for Supporting Versus Conflicting Information: Dissonance Reduction as a Means of Mood Regulation?

Abstract: Focusing on similarities between the mood regulation approach and dissonance theory, this article addresses the interplay between dissonance and mood by examining how individuals search for information after making a decision while under the influence of positive versus negative mood. Study 1 suggested that negative mood increased the preference for consonant over dissonant information after decisions, whereas positive mood led to a more balanced information search. In Study 2, participants in negative mood ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 32 publications
6
85
0
Order By: Relevance
“…(1) The influence of negative emotion of policymakers on decision time Simulation results show that, the higher the policymakers' negative emotion, the shorter the decision time they need to deal with the industrial accident, which is consistent with the conclusion of references [11] and [27]. In addition to the motivation to reduce policymakers' cognitive dissonance and improve policymakers' emotion [28], another possible reason is that, owing to the relative decrease of cognitive resources of policymakers with negative emotions as well as the decline of their cognitive abilities, policymakers can't accurately analyse the validity of each cue and their influences on schemes, so they tend to use connectionism strategy to deal with the coal mining accident, which can also more easily make policymakers form the attitude to agree with the dominant scheme and lead to a shorter decision time.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…(1) The influence of negative emotion of policymakers on decision time Simulation results show that, the higher the policymakers' negative emotion, the shorter the decision time they need to deal with the industrial accident, which is consistent with the conclusion of references [11] and [27]. In addition to the motivation to reduce policymakers' cognitive dissonance and improve policymakers' emotion [28], another possible reason is that, owing to the relative decrease of cognitive resources of policymakers with negative emotions as well as the decline of their cognitive abilities, policymakers can't accurately analyse the validity of each cue and their influences on schemes, so they tend to use connectionism strategy to deal with the coal mining accident, which can also more easily make policymakers form the attitude to agree with the dominant scheme and lead to a shorter decision time.…”
Section: Discussionsupporting
confidence: 79%
“…The other is the studies on influential factors of connectionism strategy. First of all, with regard to policymakers' emotion, some studies found that, compared with the positive emotions, policymakers with negative emotions tended to show more confirmatory biases in order to reduce cognitive dissonance when they are searching cues [11]. At the same time, negative emotions can reinforce the degree of coherence shift, and cues that are beneficial to maintain emotion are considered more important [12].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to decision making, this phenomenon has been consistently shown for both individual (Fischer, Jonas, Frey, & Schulz-Hardt, 2005;Frey, 1986;Jonas et al, 2001;Jonas & Frey, 2003;Jonas, Graupmann & Frey, 2006), and group decision making (Schulz-Hardt, Frey, Lüthgens, & Moscovici, 2000;Schulz-Hardt, Jochims, & Frey, 2002), whereas the most important practical relevance lies in the fact that this tendency can severely jeopardize decision quality (Janis, 1982;Kray & Galinski, 2003). The present research investigates whether this tendency for confirmatory information search is differently affected by gain-vs. loss-framed decision problems.…”
mentioning
confidence: 96%
“…Yet, one shortcoming of previous research on information search is that people have predominantly decided about gains or positively framed decision alternatives (e.g. which one of several positively described books or holiday trips they would prefer; e.g., Frey, 1981;Jonas & Frey, 2003;Jonas, Graupmann, & Frey, 2006). However, in real life decisionmaking, the focus often lies on risks and drawbacks of specific decision alternatives.…”
mentioning
confidence: 99%